Diagnosing Students’ Concept Understanding Using TGT Cooperative Model on Light Wave Material - Majid, Gema; Putranta, Himawan (International Journal of Education and Cognitive Sciences, 2022)
Purpose: Concept understanding is necessary for students to learn physics material. The purpose of this study was to determine the ability of students' concept understanding using TGT type cooperative model in physics material of light wave material. Methods and Materials: The research method used is qualitative research with a case study to analyze students' concept understanding using the TGT type cooperative model. The research was conducted using qualitative methods with the research subjects being students of class XI IPA B as many as 38 students. Results: This analysis revealed that the cooperative learning approach proved to be a useful strategy in supporting students' learning process. Conclusion: Based on the results of the study, it can be concluded that students' understanding of concepts using the TGT type cooperative model in class XI IPA B students at one of the MAs in Yogyakarta in the material of light waves is quite good. This can be seen from their ability to understand the basic concepts of waves, such as frequency, wavelength, and wave speed. However, in some light wave subchapter materials, students have not shown optimal understanding. This is especially true for the concepts of interference and diffraction. The application of the TGT (Teams Games Tournament) cooperative learning model can help improve concept understanding on this difficult material.